'It is like school sometimes': friendship and sociality on university campuses and patterns of social inequality. Issue 1 (2nd January 2020) - Read, Barbara; Burke, Penny Jane; Crozier, Gill
ABSTRACT: Whilst most social and educational research on friendship focuses on children at school, it remains a crucially important factor for students in higher education – and can play a key role in the maintenance, exacerbation or subversion of dominant forms of social inequalities. This paper explores the complexities of such dynamics in relation to friendship and social life at university, utilising data from an in-depth qualitative study of HE students at a UK campus university. Students stressed the importance of friendship for comfort and a sense of 'belonging'. Nevertheless, students describe the continuation of cliques, hierarchies, and exclusions that are more commonly linked to sociality at school. Despite the conception that friendship is an individual experience, it is very much influenced by social positionings such as gender, class, age, and ethnicity – having significant repercussions for students in relation to happiness and wellbeing at university.